(untitled) (Texas Journal of Engineering and Technology, 2025)
In this study, a combined ultraviolet (UV) and ultrasound (US) device was proposed for rapid and stable disinfection of drinking water from Escherichia coli and total microbial count (TMC). Experiments were conducted in a flow-through reactor in the range of US (40 kHz; 2.27 W/cm²; 0.28 s) and UV (≈26.7 W/m²; lamp depth 3.6 cm; 4.58 s) parameters. It was observed that the cavitation effects of US weakened cell walls and enhanced the damaging effect of UV radiation at the DNA level; as a result, E. coli and TMC were sharply reduced, and the microbiological stability of water (the period before regrowth) was significantly extended compared to single methods. Maintaining the UV intensity around 28–30 W/m² and placing the lamp close to the water surface increased the efficiency; in US, frequencies close to 40 kHz gave the best results. The combined mode provided high disinfection efficiency and energy efficiency with low contact time; this creates a convenient platform for practical implementation in small and medium-capacity drinking water systems.